CpSAT-1, a transcribed satellite sequence from the codling moth,Cydia pomonella - Dalíková, Martina (Jihočeská univerzita, 2017)
Satellite DNA represents one of the major components of repetitive genome components. Recent research is bringing more and more evidence about importance of this type of DNA, which can play both structural and functional roles in eukaryotic genomes. In this study, we described newly discovered satellite DNA in Cydia pomonella, CpSAT-1. Although this satDNA can be found in all chromosomes, it is surprisingly underrepresented on the W chromosome, the only heterochromatin block in Cydia pomonella genome. The CpSAT-1 is transcribed in all tested developmental stages and tissues. However, the potentially functional motives were found predominantly in non-conserved parts of monomer sequence. Thus the function of this new satellite DNA remains unknown.
CpSAT-1, a transcribed satellite sequence from the codling moth,Cydia pomonella
Keywords: satellite DNA; sex chromosomes; codling moth; expression; Cydia pomonella; satellite DNA; sex chromosomes; codling moth; expression; Cydia pomonella